Ex vivo phenotype and frequency of influenza virus-specific CD4 memory T cells. - Lucas, M; Day, C; Wyer, JR; Cunliffe, S; Loughry, A; Mcmichael, A; Klenerman, P (2004)
Recent advances in class II tetramer staining technology have allowed reliable direct ex vivo visualization of antigen-specific CD4 T cells. In order to define the frequency and phenotype of a prototype response to a nonpersistent pathogen, we have used such techniques to analyze influenza virus-specific memory CD4 T cells directly from blood. These responses are stably detectable ex vivo at low frequencies (range, 0.00012 to 0.0061% of CD4 T cells) and display a distinct "central memory" CD62L(+) phenotype.